2011
DOI: 10.1111/j.1755-5949.2011.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Psychotropics

Abstract: SUMMARYWeight gain is on the rise in the United States as is the diagnosis and treatment of mental disorders. These two phenomena are distinctly separate but tend to overlap in that most psychotropic agents approved for use in the United States are associated with the potential to induce weight gain. Metabolic disorders such as diabetes, hypercholesterolemia, and hypertension are also on the rise and often associated with weight gain and clearly associated with certain psychotropic medications. This article se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 95 publications
1
8
0
Order By: Relevance
“…This finding is in agreement with two meta-analyses which found that the duration of psychiatric illness which is a proxy for the duration of exposure to psychotropic medication is the strongest factor influencing the development of MetS [26, 31]. The longer the duration of treatment, the higher the risk for MetS since psychotropic medications cause obesity [8, 32, 33, 34, 35] through an increase in appetite for food with limited activity. Obesity leads to insulin resistance and then diabetes mellitus [36, 37], and the two conditions predispose to atherosclerosis and then HTN which are all components of MetS.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in agreement with two meta-analyses which found that the duration of psychiatric illness which is a proxy for the duration of exposure to psychotropic medication is the strongest factor influencing the development of MetS [26, 31]. The longer the duration of treatment, the higher the risk for MetS since psychotropic medications cause obesity [8, 32, 33, 34, 35] through an increase in appetite for food with limited activity. Obesity leads to insulin resistance and then diabetes mellitus [36, 37], and the two conditions predispose to atherosclerosis and then HTN which are all components of MetS.…”
Section: Discussionsupporting
confidence: 90%
“…Among the medications classified as atypical, olanzapine and clozapine may cause metabolic abnormalities [45], as well as influence weight gain [12,41,44,46,47]. In this study, we found that medication did not influence weight gain of patients throughout treatment.…”
Section: Discussionmentioning
confidence: 53%
“…This class of drugs may block the serotoninergic receptor 5-hydroxytryptamine 2C (5-HT2c), which plays a role in regulating appetite, which may, thus, increase energy intake. It may also block the histamine H1 receptor, which may deactivate the satiety center [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence demonstrates that initial postnatal weeks are critical for the postnatal development of visceral afferent reflex function, such as baroreflex and cardiopulmonary reflex. Early‐life stressors that may program blood pressure control mechanisms and modify the adaptation process of cardiopulmonary reflex will definitely increase the risk of cardiovascular (hypertension) , pulmonary (COPD and asthma) , and cardiometabolic diseases (obesity and type II diabetes) in later life. The efficient and high afferent reflex gain observed in this short period after birth may play an important role in preventing or attenuating increases in cardiovascular and cardiopulmonary systems in response to pathophysiological stresses.…”
Section: Discussionmentioning
confidence: 99%